Letter from the Editor-in-Chief - Chicheł, Adam (Journal of Contemporary Brachytherapy, 2022)
I gladly introduce the first issue of the “Journal of Contemporary Brachytherapy” this year. The 2022 year has just started, yet we face another COVID-19 high wave of infections. Whatever happens with the pandemic, we treat our patients with constantly high standards of care. Facing the problem, Yale University (USA) authors submitted their preliminary report. They verified a novel institutional approach during the COVID-19 pandemic: a single-application hybrid interstitial BT for cervical cancer. Local control outcomes demonstrated the regimen effective; however, the increased risk of mucosal toxicity need to be observed and monitored.